2017
DOI: 10.21767/2386-5180.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Male Infertility; Evidences, Risk Factors, Causes, Diagnosis and Management in Human

Abstract: Infertility has become ominous problem. On an average, about 10% of all couples face difficulty in starting a family and this creates a feeling of great personal failure, particularly in India where religious and socio-economic traditions have made it almost imperative for everyone to have children. A significant association had been found between impaired semen quality including sperm count, motility and morphology. In this review, the various contributory etiological factors i.e., exposure to heavy metals, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 104 publications
1
42
0
2
Order By: Relevance
“…where an increased testis weight with a tendency to a decreased epididymal weight in rats exposed to black tea was reported, our study demonstrated that the weights of prostate, seminal vesicles, epididymis and testes, which are testosterone-sensitive, remained unchanged. In keeping with the previous study (Wang et al, 2011), histological examination of the testes and epididymis exposed to Male infertility is caused by reduced sperm number (oligozoospermia), reduced sperm motility (asthenozoospermia), abnormal sperm morphology (teratozoospermia), reduced sperm viability (necrozoospermia) or a combination of any of these, varicocele, sexual and ejaculatory dysfunctions (Banihani et al, 2012;Guzick et al, 2001;Sharma, 2017). The current study revealed that sperm concentration was not affected by black tea; however, an improved sperm motility and sperm vitality was noted.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…where an increased testis weight with a tendency to a decreased epididymal weight in rats exposed to black tea was reported, our study demonstrated that the weights of prostate, seminal vesicles, epididymis and testes, which are testosterone-sensitive, remained unchanged. In keeping with the previous study (Wang et al, 2011), histological examination of the testes and epididymis exposed to Male infertility is caused by reduced sperm number (oligozoospermia), reduced sperm motility (asthenozoospermia), abnormal sperm morphology (teratozoospermia), reduced sperm viability (necrozoospermia) or a combination of any of these, varicocele, sexual and ejaculatory dysfunctions (Banihani et al, 2012;Guzick et al, 2001;Sharma, 2017). The current study revealed that sperm concentration was not affected by black tea; however, an improved sperm motility and sperm vitality was noted.…”
Section: Discussionsupporting
confidence: 68%
“…Male infertility is caused by reduced sperm number (oligozoospermia), reduced sperm motility (asthenozoospermia), abnormal sperm morphology (teratozoospermia), reduced sperm viability (necrozoospermia) or a combination of any of these, varicocele, sexual and ejaculatory dysfunctions (Banihani et al, 2012; Guzick et al, 2001; Sharma, 2017). The current study revealed that sperm concentration was not affected by black tea; however, an improved sperm motility and sperm vitality was noted.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of couple's infertility is due to male factors [1] . Male factors roughly could be classified into genetic (chromosomal abnormalities) or non genetic [2] . Regarding non genetic factors, at least 10% are exogenous and reversible such as the impacts of lifestyle, environmental and psychological factors [3] .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of chemical compounds have been released into the environment due to marked expansion of chemical industries worldwide. Male exposure to these chemical contaminants, which are estrogen mimics and endocrine disruptors, has been claimed as one of the causative factors contributing to the increasing male infertility [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Men who were significantly stressed had lower levels of testosterone and higher levels of FSH and LH than men with normal well-being thus reducing sperm counts and sperm morphology and motility. 45 Further, sleep disturbances may possibly have adverse effects on male fertility, as semen volume was lower in patients with difficulty in initiating sleep, including those who smoked or were overweight. 46 Treatments Semen analysis and assays for sperm chromatin integrity are the most widely utilized and best studied adjunctive diagnostics in male infertility.…”
Section: Lifestyle Factorsmentioning
confidence: 99%